2016
DOI: 10.1111/apha.12726
|View full text |Cite
|
Sign up to set email alerts
|

Is plasminogen activator inhibitor‐1 a physiological bottleneck bridging major depressive disorder and cardiovascular disease?

Abstract: Major depressive disorder (MDD) is estimated to affect one in twenty people worldwide. MDD is highly comorbid with cardiovascular disease (CVD), itself one of the single largest causes of mortality worldwide. A number of pathological changes observed in MDD are believed to contribute to the development of cardiovascular disease, although no single mechanism has been identified. There are also no biological markers capable of predicting the future risk of developing heart disease in depressed individuals. Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 116 publications
0
14
0
1
Order By: Relevance
“…Besides its roles in thrombosis and atherosclerosis, other roles related studies were relatively rare. However, studies indicated that PAI-1 is present in increased levels in various disease states (such as some forms of cancer), as well as in obesity and the metabolic syndrome [20-22]. In inflammatory conditions, PAI-1 appears to play a significant role in the progression to fibrosis, which is pathological formation of connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its roles in thrombosis and atherosclerosis, other roles related studies were relatively rare. However, studies indicated that PAI-1 is present in increased levels in various disease states (such as some forms of cancer), as well as in obesity and the metabolic syndrome [20-22]. In inflammatory conditions, PAI-1 appears to play a significant role in the progression to fibrosis, which is pathological formation of connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…20 The levels of PAI-1, along with thrombomodulin and fibrinogen, were also significantly elevated in diabetic patients with depression compared to non-depressive patients and controls. 21 Additionally, Savoy et al 22 recently measured elevated PAI-1 levels in MDD patients. It is interesting to contemplate why elevated levels of PAI-1 consistently correlate with the prevalence of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence from preclinical and clinical studies suggests that tPA and its inhibitor, PAI-1, are related to stress reaction and depression and are important fibrinolytic components. Therefore, dysfunction of the tPA–plasmin pathway could be a link between MDD and cardiovascular disease [ 83 , 84 ].…”
Section: Introductionmentioning
confidence: 99%